2016
DOI: 10.1159/000438614
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length as a Prognostic Factor for Overall Survival in Colorectal Cancer Patients

Abstract: Background/Aims: The stabilization of telomere length has important roles in the carcinogenesis of colorectal cancer. A systemic review and meta-analysis of published studies was performed to assess the prognostic role of telomere length in colorectal cancer. Methods: Pubmed and Embase were searched for eligible studies on the association between telomere length and overall survival in colorectal cancer patients. The pooled hazard ratio (HR) and corresponding 95% confidence intervals (95%CI) was calculated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
5
18
1
Order By: Relevance
“…Although the activity of telomerase was positive in most of the tumors considered in our study, we detected a significant shortening of telomeres in the tumor samples compared to the mean values of the telomere length observed in the non-tumoral paired tissues, as previously reported by others (12,25). Furthermore, according to the results obtained in the present investigation, the lower mean values of telomere length, both in tumors and in their non-tumoral paired tissues, were associated with earlier stages of Dukes, in agreement with other groups (26). Thus, these data prove that shorter telomeres are associated with cancers that, a priori, would confer a better prognosis to patients with CRC.…”
Section: Discussionsupporting
confidence: 93%
“…Although the activity of telomerase was positive in most of the tumors considered in our study, we detected a significant shortening of telomeres in the tumor samples compared to the mean values of the telomere length observed in the non-tumoral paired tissues, as previously reported by others (12,25). Furthermore, according to the results obtained in the present investigation, the lower mean values of telomere length, both in tumors and in their non-tumoral paired tissues, were associated with earlier stages of Dukes, in agreement with other groups (26). Thus, these data prove that shorter telomeres are associated with cancers that, a priori, would confer a better prognosis to patients with CRC.…”
Section: Discussionsupporting
confidence: 93%
“…Similar finding was recently reported by Hyatt et al, who revealed that patients with short telomeres had a significantly shorter overall survival. Also, in agreement with Jia and Wang; they assessed the prognostic role of telomere length in colorectal cancer that associated with poor overall survival, similar finding was reported by Barczak et al; in breast cancer. In contrast to our finding, Svenson et al found that patients with long leukocyte telomeres had a significantly worse prostate cancer‐specific and metastasis‐free survival compared to patients with short telomere length.…”
Section: Discussionsupporting
confidence: 86%
“…Telomere length as well as the proteins that play a role in telomere length are also of great interest as markers that may predict survival, functional status, and toxicity, 27,28 and studies are underway to further define the potential role of telomere length as a predictor of cancer-related outcomes. Another emerging marker of great potential benefit as a predictor of toxicity and outcomes is p16ink4a.…”
Section: Biomarkers Of Aging and Cancer Therapymentioning
confidence: 99%